Accurately intelligent film made from sodium carboxymethyl starch/κ-carrageenan reinforced by mulberry anthocyanins as an indicator. (November 2020) - Zhang, Cijian; Sun, Guohou; Cao, Lele; Wang, Lijuan
Abstract: An accurately intelligent film was obtained by casting and drying a blend solution of sodium carboxymethyl starch (CMS) and κ-carrageenan with mulberry anthocyanin extract (MAE) as an indicator, which showed different colors at different pHs. The interactions of CMS, κ-carrageenan, and MAE in the film were investigated via Fourier transform infrared spectroscopy. The film morphology and structure were evaluated by using scanning electron microscopy and X-ray diffractometry. The effects of MAE addition on the film properties were discussed. The film remained continuous and had a dense structure with the increased addition of MAE which was well-distributed in the film-forming matrix of CMS and κ-carrageenan and exhibited a good compatibility. MAE addition from 0% to 5%, increased the TS of the film from 17.56 MPa to 25.35 MPa, however, decreased the EB% and the light transmittance at 500 nm from 56.12% to 30.47% and from 62.91% to 35.98%, respectively. The incorporation of MAE made the moisture move through the film more rapidly, but no remarkable effect was exerted on the heat stability of the films. The film was applied to indicate the freshness of fish ( Cyprinus carpio var. specularis) and the red film changed to dark-blue as TVB-N of the fish reached 19.12 mg/100 g, which is close to the threshold value of freshness in the Chinese standard, showing an accurate response to the quality change. This study provides a feasible path to monitor fish freshness. Graphical abstract: Image 1 Highlights: The sodium carboxymethyl starch (CMS)/κ-carrageenan intelligent film was prepared. Mulberry anthocyanin extract (MAE) was incorporated in the intelligent film. Mulberry anthocyanin enhanced the moisture resistance and the strength of the film. The pH sensitivity and high responsiveness were shown in this intelligent film. The CCG40-M5 film can accurately monitor the freshness of fish.